An Emergent Legal Right to Repair Electronic Devices: Parsing the fine print on repair tolerances. - Samuelson, Pamela (Communications of the ACM, 2022)
The article presents the author's views on the legal right to repair electronic devices. Topics of discussion include Massachusetts's right to repair automobiles law passed in 2013, the "Nixing the Fix" report issued by the Federal Trade Commission in May 2021, and copyright and the Digital Millennium Copyright Act (DMCA).